Monitoring the external branch of the superior laryngeal nerve in thyroid surgery - Sun, Hui; Dionigi, Gianlorenzo (Annals of Thyroid; Vol 3 (April 2018): Annals of Thyroid, 2018)
The superior laryngeal nerve (SLN) is a division of the vagal nerve (VN). It derives from the inferior ganglion of VN (1,2).